Rancang Bangun Purwarupa Energy Harvesting menggunakan Piezoelektrik sebagai Pembangkit Energi Listrik - Kusnandar Kusnandar; Ni Ketut Hariyawati Dharmi; Aisyah Nurul Khairiyah (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2021)
The call to use clean and sustainable energy as an alternative energy source has grown rapidly over the past decade. This was triggered by the issue of increasing environmental pollution, the limited and decreasing amount of non-renewable energy and became one of the goals of the 2030 Sustainable Development Goals (SDG). According to the principle of conservation of energy, energy cannot be fully utilized, there is always some energy wasted. The technology to reuse